Catchment area approach for enhancing traditional terrace cultivation for sorghum crop, Kassala State, Sudan - Mustafa, Moawia; Omer, Mekki; Elamin, Elwaleed (Gezira Journal of Agricultural Science, 2018)
Farmers traditional terrace system practiced in Kassala State was not conducive for sustained grain sorghum production. The objective of this study was to determine the suitable proportional catchment area to cultivated area that produces sufficient runoff water matching the crop water requirement and improving sorghum productivity in Kassala State.This experiment was conducted in Alremeala village near Khashm Algirba town in Kassala State, for two consecutive seasons (2013/14 and 2014/15). The experimental design was a randomized complete block design with three replicates. Treatments depended on the ratio between catchment area CA (runoff area) and farm area FA, (run-on area). These ratios were: (0.5:1) or (6:12 m 2 ),  (1:1) or (12:12 m 2 ), (1.5:1) or (18:12 m 2 ), (2:1) or (24:12 m 2 ) and  without catchment (control) . Due to relatively flat surface, an artificial slope was created immediately from the end of the CA into the FA by cutting 6-10 cm deep soil layer and moved down slope to build contour bunds every 15- 20 m spacing depending on the slope as inner bunds using tractor mounted scraper or manually with a hand-hoe. The areas between bunds were chisel ploughed to 25 – 30 cm and the whole plot was bound with a U-shape border earth embankment (75 cm and 30 cm bottom and top widths, and 40 cm high) and only opens from the upper slope where runoff is coming. Sorghum variety Arfagadmak8 was planted in 80x50 cm rows and other cultural practices were performed as recommended by the ARC. Data consisted of rainfall, evapo-transpiration, runoff, soil moisture content and yield and yield components. Results indicated that the ratios 1:1, 1.5:1 and 2:1 were equally adequate to achieve improved sorghum grain and fodder yields by providing extra water harvesting and better distribution and conservation within the field. The two- year average yields were about the same for the CA: FA ratios 1:1, 1.5:1 and 2:1, but differences between them and the 0.5:1 and control were significant at the 1 % level. On average, the 1:1, 1.5:1 and 2:1 ratios produced 2312 kg/ha grain yield, increased by 20 % over the 0.5:1 ratios (1836   kg/ha) and 309% over the control (564 kg/ha). It is recommended to use a catchment area of 2:1 for improved sorghum production. نظام التروس التقليدية فى  ولاية كسلا لايساعد المزارعين فى انتاج الذرة الرفيعة. الهدف من هذه الدراسة هو تحديد الانسب لمساحة مستجمع مائي الي مساحة مزروعة لتعطى مياه جريان تتناسب مع الاحتياجات المائية للمحصول وتحسن من انتاجية محصول الذرة الرفيعة فى ولاية كسلا. أجريت هذه التجربة فى قرية الرميلة  قرب مدينة خشم القربة فى ولاية كسلا فى موسمين متتابعين (13/2014 و14/2015).استخدم تصميم القطاعات العشوائىة الكاملة في ثلاث مكررات، وخمسة معاملات تعتمد على نسبة بين مساحة للستجمع المائى CA (منطقة جريان) للمساحة منطقة المزروعة FA (منطقة مستقبل جريان) وكانت النسب كالاتى (1:0.5) او (12:6م 2 ), (1:1) او (12:12م 2 ), (1:1.5) او (12:18م 2 ), (1:2) او (12:24م 2 ) و نظام التقليدى بدون مستجمع مائي. ونسبة لسطح االمنبسط تم انحدار صناعى بين نهاية المستجمع المائي  وداخل المنطقة المزروعة وذلك بقطع وتحريك الطبقة السطحية للتربة بعمق 6-10سم لعمل حاجز ترابى كل 15-20متر تعتمد على خط الانحدار. أنشات هذه الحواجز عن طريق زحافة او يدويا.المنطقة بين الحواجز الداخلية تحرث بالمحراث الازميلي بعمق 25-30سم ونهاية المربع تاخذ شكل U. ابعاد الحواجز الترابية (75 سم العرض الاسفل و30 سم العرض الاعلى و40 سم العمق) يكون مفتوح من ناحية الانحدار حيث جريان المياه . زرع صنف الذرة ارفع قدمك  فى خطوط 50×80 سم وأجريت عليه بعض العمليات الفلاحية الاخرى الموصى بها من هيئة البحوث الزراعية. المعلومات التى تم قياسها ومتابعتها تشمل الامطاروتبخر-نتح والجريان ونسبة الرطوبة التربة والانتاج ومكونات الانتاج. تشيرالنتايج الى ان النسب 1:1, 1:1.5 و1:2  أدت الى زيادة إنتاجية  الذرة والعلف  وذلك بسبب حصاد جريان المياه وتحسين توزيعه  وحفظه داخل الحقل. متوسط الانتاج فى الموسمين متشابه فى النسب 1:2 , 1:1.5 و 1:1 ولكنه يختلف عن نسبة  1:0.5 و الزراعة التقليدية اختلاف معنوى عند مستوى 1%. متوسط انتاج الذرة فى معاملات النسب  1:1, 1:1.5 و1:2 كان 2312 كجم/هكتار يزيد بحوالى 20% عن معاملة نسبة 1:0.5 (1836 كجم/هكتار) و 309% عن معاملة الزراعة التقليدية (564 كجم/هكتار). يوصي  باتستخدم نسبة المستجمع المائي 1:2 لتحسين انتاجية الذرة.